LACK OF COSTUMER VISITATION ANALYSIS USING NEW SEVEN QC TOOLS (Case study in Acasta Restaurant) - Mega Aulia Silviadara; Wiwik Budiawan (Program Studi Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2016)
Companies in the service industry have its own parameters in terms of quality and quantity which is used as a consideration of measures prior to purchasing a particular service. In many cases, it is found that the number of customers in a restaurant is the effect of the quality of the service provided. As for this exact case, management has complained of the minimum amount of customers visiting. Therefore, a research based on the new seven tools method has been carried in an attempt to resolve this management issue. With the aforementioned method, there were a few identified conflicts found in the restaurant’s services, one of which is the lack of advertising, delaying service, absence of a dynamic atmosphere along with location that is deemed un-strategic. With this research, Acasta have come up with different steps of improvement aimed to increase the quality of service and the number of customer visitations. In order to improve in the services, calculations were obtained towards the estimated time on each of the improvement processes. As a result of those calculation, it is known that the restaurant has a big potential. In implementing this improvement, there are two important issues to take note one, first is the span of time it takes and the priority of order performed. From 16 solutions there are 3 best solution for this research; Adding some waiters/waitresses to speed up service, purchase more fans/install air conditioner (depending on budget), and create a bigger signboard.